The Governance Game - Banuri, Sheheryar (World Bank, Washington, DC, 2017)
In this paper, the authors use the lab to test a series of policy proposals designed to constrain rent-seeking behaviour in a policymaking context. The baseline governance game is conducted in the following way: subjects are randomly assigned to groups of four, with one subject randomly selected to be the “policymaker", while the other three are the “citizens”. Citizens are informed that they can use their endowments to contribute to a group account. Any amount contributed to the group account are doubled. Once citizens have made their contribution decisions, the policymaker observes the contribution decisions of each citizen, and the total amount in the group account. The policymaker formulates a distribution “policy” to distribute the tokens among all four group members. The game is repeated for 20 rounds. With this basic framework, the authors implement and test the effect of three institutions designed to constrain policymaker rent-seeking behaviour: voting, policy commitment, and punishment. The results show that voting and enforced commitment are the most effective policy mechanisms to constrain rent-seeking, and improve citizen welfare. The authors find policymaker punishment regimes to be largely ineffective, both in reducing rent-seeking and improving welfare of citizens.